Methodological dilemmas: gatekeepers and positionality in Bradford - Sanghera, Gurchathen S; Thapar-Björkert, Suruchi (Ethnic and racial studies, 2008)
This paper explores the ever-evolving relationship between gatekeepers and the researcher, and the ways in which it may facilitate, constrain or transform the research process by opening and/or closing the gate. We explore the methodological issue of positionality and discuss the ways in which gatekeepers drew on different axes of the researcher's identities - religion, ethnicity, gender and age - in ambiguous and contradictory ways. In analysing this relationship, we locate the discussion within its historical context, as we contend that contextuality influenced the way gatekeepers positioned the researcher. This paper draws on the field experiences of the first author in four inner-city neighbourhoods in Bradford, West Yorkshire, a northern city with a well-established Pakistani Muslim community that has become synonymous with the Rushdie affair and the 1995 and 2001 urban disturbances.